2020
DOI: 10.3384/njvet.2242-458x.20101108
|View full text |Cite
|
Sign up to set email alerts
|

Digitala körsimulatorer i yrkesutbildning: Utmaningar och möjligheter

Abstract: This article discusses the didactical challenges and opportunities of driving simulator supported teaching and learning, mediated through digital technology in vocational educational and training through the example of driving simulators. We highlight relevant research on simulator-supported teaching and the need for practice-based, empirically driven research. The study is part of a larger project that focuses on the implementation of simulator environments in three secondary schools in the natural resource p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
7
0
3
Order By: Relevance
“…Limited fidelity of a simulator is generally considered as a drawback compared to driver training on the roads. Nevertheless, it has been reported that further developments in driving simulators should not necessarily be aimed at increasing fidelity but at the improvement of didactics and courseware instead (Gustavsson et al, 2020). One aspect to consider regarding this is the different groups' training, partly the actual training time the students received within the scheduled time but also pedagogical aspects, such as proximity to instructors, opportunity to ask questions and get constructive feedback up close.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited fidelity of a simulator is generally considered as a drawback compared to driver training on the roads. Nevertheless, it has been reported that further developments in driving simulators should not necessarily be aimed at increasing fidelity but at the improvement of didactics and courseware instead (Gustavsson et al, 2020). One aspect to consider regarding this is the different groups' training, partly the actual training time the students received within the scheduled time but also pedagogical aspects, such as proximity to instructors, opportunity to ask questions and get constructive feedback up close.…”
Section: Discussionmentioning
confidence: 99%
“…Using simulators (if this could be assumed to be an equivalent learning activity to achieve a certain learning objective in police education) could increase teaching and practice opportunities (mass training); generate more individual feedback (pedagogical effect) on certain aspects of driving; and provide the opportunity to gradually increase the cognitive load (dual tasking such as communicating via radio, using GPS, etc.) in a safe environment (e.g., Gustavsson et al, 2020;Zahabi et al, 2021). Furthermore, researchers and instructors could gain increased knowledge about simulator-based training as a pedagogical tool, which could possibly lead to the development of police education in general and reduce the emissions this learning activity generates daily, one of Sweden's 16 environmental quality objectives in relation to Agenda 2030 (Naturvårdsverket, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…En väsentlig aspekt är vad som faktiskt sker både planerat och oplanerat i en digital undervisningsmiljö, det vill säga när förutsättningarna förändras. En annan fråga handlar om vad det digitala verktyget faktiskt främjar och vilka didaktiska konsekvenser det för med sig (Gustavsson, et al, 2020). Hansson (2013) studerar införande av digital teknik som en del av en skolas systematiska kvalitetsarbete och finner intressemotsättningar mellan lärares undervisningsrelaterade frågor och skolledningens fokus på organisation.…”
Section: Bakgrundunclassified
“…Till exempel inom vårdutbildning krävs simulerad färdighet innan studenten eller eleven kan öva på en patient. Vidare finns renodlade pedagogiska och didaktiska skäl (Gustavsson et al, 2020), det vill säga simulatorstödd undervisning som ett led i lärandeprocessen, vilket innebär att det digitala verktyget stödjer lärandeprocessen i mer allmän mening och därmed ersätter eller kompletterar autentisk undervisning. En sammanställning av iakttagelser (de Winther et al, 2012) visar att körsimulatorer kan bidra med specifika reproducerbara övningar, samla data om elevens kunskaper och ge återkoppling under övningen samt bidra till kunskap om säkerhetsaspekter.…”
Section: Bakgrundunclassified
See 1 more Smart Citation